Hubungan Konsep Diri dan Dukungan Sosial Orang Tua Terhadap Kematangan Karier Siswa MA Madania - Azis Rahmat Ma’rufi; Mujidin Mujidin; Yuzarion Yuzarion (SEKOLAH TINGGI AGAMA ISLAM AL-HUSAIN MAGELANG, 2020)
The purpose of this study is to test: 1) The relationship between self-concept and parents' social support to the career maturity of MA Madania students; 2) The relationship between self-concept and career maturity of MA Madania students; and 3) The relationship between social support of parents to the career maturity of MA Madania students. The sample of this research was grade XII students in MA Madania, totaling 53 students taken using saturation sampling technique. Data retrieval is done using three scales, namely the scale of career maturity, self-concept scale, and the scale of parental social support. Data were analyzed by multiple regression analysis and correlation techniques. The results of the multiple regression analysis obtained an F count of 27.325 with a significance of 0.000 <0.05, meaning that there is a relationship between self-concept and social support of parents to career maturity. Correlation analysis results obtained r = 0.604 with a significance of 0,000 <0.05, meaning that there is a relationship between self-concept and career maturity. The correlation analysis results obtained r = 0.636 with a significance of 0,000 <0.05, meaning that there is a relationship between social support of parents to career maturity. Contribution of the effectiveness of variables X1 and X2 to variable Y is 0.522 or 52%, meaning that self-concept and social support of parents can influence career maturity. Contribution of the effectiveness of variable X1 to variable Y is 0.365 or 36%, meaning that self-concept can influence career maturity. Contribution of the effectiveness of variable X2 to variable Y is 0.404 or 40%, meaning that social support from parents can influence career maturity. Based on the results of the study it can be concluded: 1) There is a relationship between self-concept and parents' social support to the career maturity of MA Madania students; 2) There is a positive relationship between self-concept and career maturity of MA Madania students; and 3) There is a positive relationship between social support of parents on the career maturity of MA Madania students.